Optimal Water Use and Cropping Pattern for Thrithala Regulator-Cum-Bridge Project - Saritha E K (Department of Land and Water Resources and conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 2000)
Reservoir projects involve huge financial investment and hence, every drop of water stored in the reservoir must be utilised very judiciously. Allocation of water in the case of multi-purpose projects among various competing needs such as drinking water, irrigation, pisciculture, downstream flow, etc. is a matter of great concern. Hence, formulation of optimal operational policies for reservoirs has become highly essential to improve their financial viability, social acceptability and overall performance. So a study has been undertaken for a regulator-cum-bridge under construction at Thrithala in Palakkad district of Kerala state in Indian peninsular with the specific objectives of determining the optimum water allocation of the reservoir for meeting various demands on it and obtaining the optimum cropping pattern for the command area. A linear programming model was formulated to optimize the reservoir operation of the multipurpose project with the objectives of Drinking water demand, Irrigation demand, Pisciculture demand, and Downstream flow demand, in the order of priority. The deviations of the allocations from the targets to be achieved were minimized by introducing penalty coefficients to each deviation according to their order of priority. Using the irrigation allocation from this model, another Linear Programming model was formulated to obtain the optimal cropping pattern for the command area. Both models were solved using Excel Solver software package. The optimal operational plan and the optimal cropping. pattern obtained were compared with the operating plan and cropping pattern proposed by the irrigation department. The optimal operation plan with the incorporation of additional objectives was found to be more socially acceptable and economically viable. The optimal cropping pattern showed that there is more than 100% increase both in the net benefit as well as in the net area irrigated.